Role of primary sensorimotor cortices in generating inhibitory motor response in humans - Ikeda, Akio; Ohara, Shinji; Matsumoto, Riki; Kunieda, Takeharu; Nagamine, Takashi; Miyamoto, Susumu; Kohara, Nobuo; Taki, Waro; Hashimoto, Nobuo; Shibasaki, Hiroshi (Brain (London, England : 1878), 2000)
To clarify the mechanism by which inhibitory motor responses such as cortical negative myoclonus are generated in humans, three patients with medically intractable partial epilepsy (two with frontal lobe epilepsy and one with parietal lobe epilepsy) were studied by means of direct cortical stimulation with a single electric pulse through subdural electrodes. All underwent chronic long-term video/EEG monitoring, cortical mapping by 50 Hz electric cortical stimulation and recording of cortical somatosensory evoked potentials with chronically implanted subdural grid electrodes (3 mm in diameter and centre-to-centre distance of 1 cm) to map both epileptogenic and functional zones. After these clinical evaluations, cortical stimulation by single electric pulse (0.3 ms duration, 1 Hz) was carried out through pairs of subdural electrodes located at the primary sensorimotor area (MI-SI), pre-supplementary motor area (pre-SMA) and lateral negative motor area (lateral NMA), while surface EMG was recorded from the muscles of the contralateral hand. The results showed that (i) in all subjects, single pulse stimulation of MI-SI elicited a motor evoked potential (MEP) followed by a silent period (SP) in the contralateral distal hand muscles, the latter lasting 300 ms after the stimulus. The duration of SP was proportional to the size of the preceding MEP. In one subject, SP without any preceding MEP was elicited, and, in another subject, there was a short SP immediately before MEP in the contralateral thenar muscle. (ii) Following the stimulation of either pre-SMA or lateral NMA, no SP was observed. It is concluded that the inhibitory mechanism within the MI-SI, but probably not in the non-primary motor areas, either closely linked to or completely independent of excitation, most likely plays an important role in eliciting brief negative motor phenomena such as cortical negative myoclonus or SP.